Partition Coefficient Ratios and Tumour Perfusion Studied with 85mKr and 133Xe - Heikkonen, J.; Mäntylä, M.; Perkkiö, J. (Nuklearmedizin - NuclearMedicine, 1987)
The relative partition coefficients of krypton and xenon, and the regional blood flow in 27 superficial malignant tumour nodules in 22 patients with diagnosed tumours were measured using the 85mKr- and 133Xe-clearance method. In order to minimize the effect of biological variables on the measurements the radionuclides were injected simultaneously into the tumour. The distribution of the radiotracers was assumed to be in equilibrium at the beginning of the experiment. The blood perfusion was calculated by fitting a two-exponential function to the measuring points. The mean value of the perfusion rate calculated from the xenon results was 13 ± 10 ml/(100 g-min) [range 3 to 38 ml/(100 g-min)] and from the krypton results 19 ± 11 ml/(100 g-min) [range 5 to 45 ml/(100 g-min)]. These values were obtained, if the partition coefficients are equal to one. The equations obtained by using compartmental analysis were used for the calculation of the relative partition coefficient of krypton and xenon. The partition coefficient of krypton was found to be slightly smaller than that of xenon, which may be due to its smaller molecular weight.Die relativen Verteilungskoeffizienten von Krypton und Xenon sowie die regionale Durchblutung in 27 oberflächlichen malignen Tumorknoten bei 22 Patienten mit gesicherten Tumoren wurden mittels der 85mKr- und 133Xe-Clearance-Methode bestimmt. Um Effekte biologischer Variabler auf die Messung einzuschränken, wurden die Radionuklide gleichzeitig in den Tumor injiziert. Ein Äquilibrium in der Verteilung des Radiotracers zu Beginn der Untersuchung wurde angenommen. Die Durchblutung wurde mittels Fit zweier Exponentialfunktionen an den Meßpunkten berechnet. Für Xenon wurde eine mittlere Flußrate von 13 ± 10 ml/ (100 g-min) [Bereich 3 bis 38 ml/ (100 g-min)] und für Krypton von 19 ± 11 ml/(100 g-min) [Bereich von 5 bis 45 ml/(100 g-min)] berechnet. Diese Werte gelten für die Annahme eines Verteilungskoeffizienten von 1. Die Gleichungen, welche sich aus der Kompartmentanalyse ergaben, wurden für die Berechnung des relativen Verteilungskoeffizienten von Krypton und Xenon benützt. Hierbei ergab sich für Krypton ein etwas geringerer Wert als für Xenon, was mit dessen kleineren Molekulargewicht Zusammenhängen könnte.